Analisis Yuridis Terhadap Tingkat Efisiensi Penyelesaian Perselisihan Hasil Pemilukada oleh MK - Iqbal Khastama; Dodi Jaya Wardana (UNES Law Review, 2023)
The results of votes obtained in official legislative elections by the KPU often receive unsatisfactory responses from election participants. This was triggered by intent, negligence, technical errors, administrative weaknesses or human error. In order to realize democratic elections, the following principles should be applied; honest; independent; orderly, fair, legal certainty; prioritizing public interests; openness and transparency; proportionality; professionalism; accountability; efficiency; and effectiveness. The Constitutional Court should have credibility and professionalism as a decision maker in election disputes. In 2019, 676 PHPU cases were reported to the Constitutional Court and 1135 other cases related to Kada PHP. UU no. 7 of 2017" has been ratified as a codification of election law, in order to create consistency and legal certainty as well as effective and efficient elections. Brazil, as one of the countries with the title of an effective election system, has an institution called "the Electoral Judges for municipal elections", which can be used as a reference by Indonesia in resolving disputes over regional election results. The method used in this research is normative, with explanatory explanations, using various library sources.